The Relationship of Music Listening Habits, Their Utilization When Learning Mathematics Against the Learning Outcomes of Mathematics Subjects of Class XI Students in Vocational High Schools in Pika Semarang - Pramudhita, Chatarina Ria; utomo, udi (Jurnal Seni Musik, 2019)
Based on the experience of researchers, many as young as teenagers tend to be lazy and bored having to struggle with the subject continuously. Burnout can be seen in adolescence is required to repeat the lessons learned in school. This makes most teenagers often forget about the duties and responsibilities to learn and do the work at night. The formulation of the problem is as follows; (1) How high frequency music listening habits when studying Maths at grade students at PIKA Semarang VOCATIONAL HIGH SCHOOL ?, (2) How high is the frequency of the use of music when studying ?, (3) How high is the result of learning mathematics in grade students PIKA Semarang VOCATIONAL HIGH SCHOOL ?, (4) Is there a relationship habit of listening to music and use while learning to learning outcomes in Mathematics class XI VOCATIONAL HIGH SCHOOL PIKA Semarang? This study assessed using a quantitative approach. Data collection techniques include observation and questionnaire study. Mechanical examination of the validity of data using the reliability test, validity test. Data analysis technique used is descriptive analysis percentage, normality test, homogentias, hypothesis testing. Based on the results of research and discussion, it can be concluded the relationship between music listening preferences and utilization of listening to music while studying the learning outcomes in Mathematics is as follows; (1) The average yield of joy listening to music while studying in class XI VOCATIONAL HIGH SCHOOL PIKA Semarang considered good. (2) The average frequency of utilization of listening to music while studying in class XI VOCATIONAL HIGH SCHOOL PIKA Semarang considered good. (3) There is a significant relationship between A listen to music and use of listening to music while studying the learning outcomes in Mathematics. Based on this conclusion above, the advice can be delivered, among others: (1) Music as a means to increase the concentration in the study, preferably in choosing the type of music must be considered as well as possible, (2) For future studies different of types of music can be studied in increasing concentrations studied, so will the obtained results more valid.